Respuestas
Respuesta dada por:
0
Usaremos estas propiedades:
![{x}^{n} = n {x}^{n - 1} \\ c = 0 {x}^{n} = n {x}^{n - 1} \\ c = 0](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7Bn%7D++%3D+n+%7Bx%7D%5E%7Bn+-+1%7D++%5C%5C+c+%3D+0)
Resolviendo:
![5 {x}^{2} - 3 x+ 1 = 10x - 3 \\ {x}^{4} + 3 {x}^{2} - 6 = 4 {x}^{3} + 6x 5 {x}^{2} - 3 x+ 1 = 10x - 3 \\ {x}^{4} + 3 {x}^{2} - 6 = 4 {x}^{3} + 6x](https://tex.z-dn.net/?f=5+%7Bx%7D%5E%7B2%7D++-+3+x%2B+1+%3D+10x+-+3+%5C%5C++%7Bx%7D%5E%7B4%7D++%2B+3+%7Bx%7D%5E%7B2%7D++-+6+%3D+4+%7Bx%7D%5E%7B3%7D++%2B+6x)
C= Constante.
n= Exponente.
x= Variable.
Resolviendo:
C= Constante.
n= Exponente.
x= Variable.
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años